Analisis Dan Perancangan Sistem Informasi Penggajian Di PT. BIG SURABAYA - Wulandari, Lauw; Tanuwijaya, Haryanto; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2012)
PT. BIG Surabaya is a multi-company that has the department include Banquet and Restaurant, T-Bar, Office Park, and Regency. PT. BIG Surabaya in the development of his company faced several problems in the payroll system. Analysis and design of payroll information system at PT. BIG Surabaya can give a result of employee payroll information system design and to help devise a system for the accurate calculation of employee payroll. With the use of computerized systems is expected to address the problem in the PT. BIG Surabaya, which can help speed up the calculation of payroll and tax calculations in PT. BIG Surabaya. Keywords: analysis and design system and payroll information system.